(untitled) - Kornicki, Peter (Honolulu, 2001)
This monograph covers every major aspect of the book in traditional Japan: its place in Japanese history; books as material objects; manuscript cultures; printing; the Edo period book trade; authors and readers; and importation and exportation.
Keywords: Books,Printing; History,History; Japan,Japan